Operational Strategies to Reduce Casualty Clinic Crowding: Findings From an Ophthalmology Audit and Re-Audit - Gunasekaran, Thiruvarasu; Valaiyuthan, Jeevindran; Tajunisah, Iqbal (Malaysian Journal of Medical Sciences, 2026)
Efficient appointment management is essential for maintaining optimal patient flow in high-volume ophthalmology casualty services. A multitude of factors drive clinic overcrowding and delays in service delivery. This audit aimed to evaluate appointment management performance in an ophthalmology casualty clinic by analysing walk-in rates, overbooking practices, compliance with staggered appointment times, and clinic completion time. A prospective audit was conducted over 30 working days in the Ophthalmology Casualty Clinic at General Hospital Kuantan. Data were collected using a standardised daily form that captured walk-in attendance, scheduled appointment slots, patient arrival times, and the total time required for physicians to complete casualty consultations. Audit standards were defined as a walk-in rate of ≤ 20%, an overbooking rate of ≤ 10%, compliance with staggered appointment times of ≥ 80%, and clinic completion within 5 h. A total of 796 patients attended the clinic during the audit period. The walk-in rate was 43.2%, exceeding the predefined standard. Overbooking rate and compliance with staggered appointment times met the audit standards. The mean clinic completion time was 6.2 h, exceeding the target duration. Several improvement measures were implemented over a three-month period. These included introducing a triage checklist, allocating urgent follow-up slots, monitoring peak attendance trends, and increasing staffing during peak hours. A re-audit was subsequently conducted over a two-month period. The walk-in rate decreased to 25.4%, and the mean clinic completion time improved to 4.8 h. This audit demonstrates that targeted operational interventions may improve clinic efficiency and patient flow in ophthalmology casualty services.